2012
DOI: 10.1016/j.jcp.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to sub-grid surface tension for LES of two-phase flows

Abstract: In two-phase flow, the presence of inter-phasal surface -the interface -causes additional terms to appear in LES formulation. Those terms were ignored in contemporary works, for the lack of model and because the authors expected them to be of negligible influence. However, it has been recently shown by a priori DNS simulations that the negligibility assumption can be challenged. In the present work, a model for one of the sub-grid two-phase specific terms is proposed, using deconvolution of the velocity field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 54 publications
1
65
0
Order By: Relevance
“…It is well known that through mass weighted filtering of the transport momentum equations more sub-grid closure terms, in addition to the well-known single phase sub-grid stress tensor presented above, can result in momentum, continuity and VOF advection equations. These additional terms and among them the interfacial ones with suggested modeling have been discussed in a number of papers (Aniszewski et al, 2012;Gohrokhovski and Herrmann, 2008;Labourasse et al, 2007;Lakehal, 2010Lakehal, , 2005Lakehal and Liovic, 2011;Larocque et al, 2010;Lakehal, 2007, 2012;Reboux et al, 2006). These extra terms are not considered in this work and the question remains how important their contribution to the solution is.…”
Section: Mathematical Description and Numerical Modelingmentioning
confidence: 96%
See 1 more Smart Citation
“…It is well known that through mass weighted filtering of the transport momentum equations more sub-grid closure terms, in addition to the well-known single phase sub-grid stress tensor presented above, can result in momentum, continuity and VOF advection equations. These additional terms and among them the interfacial ones with suggested modeling have been discussed in a number of papers (Aniszewski et al, 2012;Gohrokhovski and Herrmann, 2008;Labourasse et al, 2007;Lakehal, 2010Lakehal, , 2005Lakehal and Liovic, 2011;Larocque et al, 2010;Lakehal, 2007, 2012;Reboux et al, 2006). These extra terms are not considered in this work and the question remains how important their contribution to the solution is.…”
Section: Mathematical Description and Numerical Modelingmentioning
confidence: 96%
“…On the other hand, the relative importance of these terms has also been studied through a priori DNS simulations on very specific flows by Labourasse et al (2007) and Larocque et al (2010). Attempts at modeling the unresolved surface tension force is for instance considered by Aniszewski et al (2012) and a current state of art review is included in Gorokhovski and Herrmann (2008). It can be said that the most important term remains the inertia terms as in single phase flows which are included in the present study and which might require special modeling near interfaces as done, for instance, by Liovic and Lakehal (2007) while the other terms remain relatively weak (Larocque et al, 2010).…”
Section: Mathematical Description and Numerical Modelingmentioning
confidence: 99%
“…The SAILOR code was used previously in various studies including laminar/turbulent transition in near-wall flows [22], free jet flows [23,24], multi-phase flows [25] and flames [26,27]. The SAILOR code is based on a projection method with time integration performed by a predictor-corrector (Adams-Bashforth / Adams-Moulton) method [28].…”
Section: Les Solvermentioning
confidence: 99%
“…Two main conclusions arise from these studies: new subgrid terms have to be modeled when the LES of two-phase flows is undertaken and the magnitude of these subgrid terms strongly varies depending on the considered physical configuration so that none of these subgrid terms can be neglected a priori, except perhaps the vis-cous subgrid term. Concerning the modeling of the two-phase LES subgrid terms, most advanced works have been devoted to the inertial and capillary terms with formulations based on Smagorinsky or deconvolution like approaches [12,33]. None of these LES models have clearly demonstrated that it was possible to perform a LES of resolved scale interfaces with success, except perhaps [12] for the atomization of a fuel jet.…”
Section: Introductionmentioning
confidence: 99%
“…We have used a 7 th order of approximation for G −1 , instead of a classical 5 th order found in literature [9,33], because we have observed better accuracy of modeled subgrid terms compared to filtered DNS terms. For higher orders, no significative improvements have been found.…”
mentioning
confidence: 99%